Calculating Pulmonary-Mode-Lethality Risk Avoidance Associated with Radionuclide Decorporation Countermeasures Related to a Radiological Terrorism Incident - Bobby R. Scott (SAGE Publishing, 2010)
Planning for and managing radiological terrorism incidents that involve the release of radionuclides from a dirty bomb requires considering the potential lifesaving impact of protective radionuclide decorporation countermeasures (e.g., lung lavage). Lung lavage therapy could prevent deaths via the pulmonary mode (which involves radiation pneumonitis and fibrosis) by reducing the radiation dose to the lung from inhaled radionuclides. The risk avoidance ( RAV ) assessment framework introduced in a related paper is used to evaluate the pulmonary-lethality-mode RAV due to lung lavage and the associated risk avoidance proportion ( RAP ) for hypothetical inhalation-exposure scenarios. The lethality RAV is a measure (on a scale from 0 to 1) of the actual risk reduction associated with the applied protective countermeasures. The lethality RAP is the lethality RAV divided by the lethality risk when no protective countermeasures are employed and is a useful measure of the efficacy of the countermeasures applied. Examples of pulmonary-mode lethality RAV and RAP calculations are presented for hypothetical scenarios involving lung lavage to remove beta and/or gamma-emitting radionuclides that are inhaled in highly insoluble forms. The approach presented could be used to develop optimal schemes for applying lung lavage therapy following a terrorist incident involving a dirty bomb.